Comparing the content of leadership theories and managers' shared perceptions of effective leadership: A Q-method study of trainee managers in the English NHS. (August 2013) - Freeman, Tim
Health service managers face potential conflicts between corporate and professional agendas, a tension sharpened for trainees by their junior status and relative inexperience. While academic leadership theory forms an integral part of contemporary management development programmes, relatively little is known of trainees' patterned subjectivities in relation to leadership theories. The objective of this study was to explore such subjectivities within a cohort of trainees on the National Health Service Graduate Management Training Scheme (NHS GMTS), a 'fast-track' programme which prepares graduate entrants for director-level health service management posts. A Q-method design was used and four shared subjectivities were identified: leadership as collaborative social process ('relational'); leadership as integrity ('moral'); leadership as effective support of subordinates ('team'); and leadership as construction of a credible leadership persona ('identity'). While the factors broadly map onto competencies indicated within the NHS Leadership Qualities Framework which underpin assessments of performance for this student group, it is important not to overstate the governance effect of the assessment regime. Rather, factors reflect tensions between required competencies, namely the mobilisation of diverse interest groups, the ethical base of decisions and the identity work required to convince others of leadership status. Indeed, factor 2 ('moral') effectively defines leadership as the embodiment of public service ethos.